2020
DOI: 10.1177/1558925020983561
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibration of knitted spacer fabric under harmonic excitation

Abstract: Knitted spacer fabrics can be an alternative material to typical rubber sponges and polyurethane foams for the protection of the human body from vibration exposure, such as automotive seat cushions and anti-vibration gloves. To provide a theoretical basis for the understanding of the nonlinear vibration behavior of the mass-spacer fabric system under harmonic excitation, experimental, analytical and numerical methods are used. Different from a linear mass-spring-damper vibration model, this study builds a phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Luo et al [4] applied this method to analyze dynamic characteristics in a rubber-based rail fastener system, utilizing the superposition principle for hysteresis loop simulations on rubber components. Chen et al [5] extended this ap-preach to fabric spacers, introducing asymmetric elastic force and fractional differ-ential force. Roncen et al [6] expanded the Numerical Approach using the harmonic balance and shooting method, focusing on the softening effect in a rubber isolator subjected to random exciting forces.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [4] applied this method to analyze dynamic characteristics in a rubber-based rail fastener system, utilizing the superposition principle for hysteresis loop simulations on rubber components. Chen et al [5] extended this ap-preach to fabric spacers, introducing asymmetric elastic force and fractional differ-ential force. Roncen et al [6] expanded the Numerical Approach using the harmonic balance and shooting method, focusing on the softening effect in a rubber isolator subjected to random exciting forces.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al 4 applied this method to analyze dynamic characteristics in a rubber-based rail fastener system, utilizing the superposition principle for hysteresis loop simulations on rubber components. Chen et al 5 extended this approach to fabric spacers, introducing asymmetric elastic force and fractional differential force. Roncen et al 6 expanded the Numerical Approach using the harmonic balance and shooting method, focusing on the softening effect in a rubber isolator subjected to random exciting forces.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been carried out to study the vibration properties of knitted spacer fabrics from different perspectives. 3444 Frydrysiak and Pawliczak 41 found that knitted spacer fabric has the advantage of having much lower thickness than typical sponges as vibration damping inserts in workplace seating. Krumm et al.…”
mentioning
confidence: 99%
“…Chen et al. 34,44 have studied the nonlinearity in the frequency responses of weft-knitted spacer fabrics using experimental, theoretical and numerical methods.…”
mentioning
confidence: 99%